Performance of a combined bacteria/zeolite permeable barrier on the rehabilitation of wastewater containing atrazine and heavy metals - Silva, Bruna Andreia Nogueira Airosa (2023)
Several chemicals, such as pesticides and heavy metals, are frequently encountered together in environment matrices, becoming a priority concerning the prevention of their emissions, as well as their removal from the environment. In this sense, this work aimed to evaluate the effectiveness of a permeable biosorbent bio-barrier reactor (PBR) on the removal of atrazine and heavy metals (copper and zinc) from aqueous solutions. The permeable bio-barrier was built with a bacterial biofilm of R. viscosum supported on 13X zeolite. One of the aims of this work is the investigation of the toxic effects of atrazine, copper and zinc on the bacterial growth, as well as the assessment of their ability to adapt to repeated exposure to contaminants and to degrade atrazine. The growth of R. viscosum was not affected by concentrations of atrazine bellow 7 mg/L. However, copper and zinc in binary solutions were able to inhibit the growth of bacteria for all the concentrations tested (5 to 40 mg/L). The pre-acclimation of the bacteria to the contaminants allowed for an increase of 50% of the bacterial growth. Biodegradation tests showed that 35% of atrazine was removed/degraded, revealing that this herbicide is a recalcitrant compound that is hard to degrade by pure cultures. The development of a PBR with R. viscosum supported on zeolite was successfully performed and the removal rates were 85% for copper, 95% for zinc and 25% for atrazine, showing the potential of the sustainable and low-cost technology herein proposed.